Mood Types Analysis on Stand Up Comedy Titled "Don't Lose Your Accent / Learning Accents" by TREVOR NOAH (Pay Back The Funny) - Yuyun Ilantri; Wawan Gunawan (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2025)
Humor is a universal language that cuts across cultural barriers. Trevor Noah's stand-up special "Don't Lose Your Accent / Learning Accents are good examples of humor in the classroom. The theory of systemic functional linguistics says language functions as a system for meaning-making. A positive and fun atmosphere in the learning environment can increase motivation and interest in the language. Moreover, it often involves wordplay, puns, and linguistic creativity. Engaging in language play helps learners become more comfortable with the structure and flexibility of the language, fostering linguistic creativity and a deeper understanding of how the language works. In hence, Incorporating humor into language learning can be done through a variety of means, including funny anecdotes, jokes, cartoons, humorous videos, and interactive activities. It's essential to strike a balance between humor and educational content, ensuring that the humor enhances the learning experience rather than becoming a distraction